2021
DOI: 10.1590/1980-5373-mr-2021-0100
|View full text |Cite
|
Sign up to set email alerts
|

Sliver Doped Sodium Antimonate with Greatly Reduced the Band Gap for Efficiently Enhanced Photocatalytic Activities Under Visible Light (Experiment and DFT Calculation)

Abstract: In this work, Ag doped NaSbO 3 (ANS) was successfully synthesized and applied an efficient visible light photocatalyst. The properties of catalyst were fully characterized, and DFT (the density functional theory) computation was utilized to investigate the photocatalytic mechanism. The various characterization findings proved that Ag atoms were perfectly doped into NaSbO 3 crystals, which greatly reduced the band gap, and made ANS catalyst exhibit excellent visible light absorption performance. In addition, AN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 63 publications
(63 reference statements)
0
1
0
Order By: Relevance
“…Figure 8 b,c presents the first-order kinetic [ 34 , 35 ] fitting results of the photocatalytic process in different reaction systems, and the original data was obtained from Figure 8 a. It was observed that the first-order kinetic equation displayed excellent fitting results for all degradation systems, and all the fitting R 2 values were above 0.94.…”
Section: Resultsmentioning
confidence: 93%
“…Figure 8 b,c presents the first-order kinetic [ 34 , 35 ] fitting results of the photocatalytic process in different reaction systems, and the original data was obtained from Figure 8 a. It was observed that the first-order kinetic equation displayed excellent fitting results for all degradation systems, and all the fitting R 2 values were above 0.94.…”
Section: Resultsmentioning
confidence: 93%